A PVC / polyester composite outer sheath material for high-shielding cable and its preparation method

By using modified conductive carbon black and PVC/polyester composite materials in high-shielding cable materials, the problems of poor dispersion and poor interface bonding of conductive carbon black are solved, and efficient electromagnetic shielding performance and good mechanical properties are achieved, reducing production costs.

CN119505445BActive Publication Date: 2025-04-22TAIZHOU TIANDAYUAN TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510091406.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-22
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The existing high-shielding cable outer sheath materials have problems such as poor dispersion of conductive carbon black, poor interface bonding, unsatisfactory electromagnetic shielding effect and high cost.

Method used

Using PVC/polyester composite materials, the preparation methods of modified conductive carbon black include ultrasonic dispersion, graft modification and surface packaging to improve the dispersion and interface bonding of conductive carbon black, and through the optimization of the assembly distribution ratio and processing technology, the effective distribution of conductive fillers and the improvement of electromagnetic shielding performance are achieved.

Benefits of technology

It realizes excellent electromagnetic shielding performance, good mechanical properties and processing performance of high-shield cable materials, and at the same time reduces the amount of conductive filler, reduces production costs, and meets the various technical requirements of high-shield cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a PVC / polyester composite outer sheath material for high-shielding cables and a preparation method thereof, and relates to the technical field of cables. The outer sheath is made of the following components by weight: 100 parts of PVC, 30-50 parts of polypropylene adipate, 20-40 parts of inorganic fillers, 4-12 parts of modified conductive carbon black, 1-3 parts of stabilizers, 1-3 parts of antioxidants, and 0.5-2 parts of silane coupling agents; the material has excellent electromagnetic shielding performance and mechanical strength, and exhibits good weather resistance and corrosion resistance; has a wide processing window and excellent processing performance; while ensuring various performances, reduces the amount of conductive fillers added, effectively reduces the production cost, can meet various technical requirements of high-shielding cables, and has important application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cables, and in particular to a PVC / polyester composite outer sheath material for high-shielding cables and a preparation method thereof. Background Art

[0002] The cable outer sheath mainly plays a protective and insulating role, and commonly used materials include polymer materials such as PVC, polyethylene, and polyurethane. PVC has good processing performance and weather resistance, and is low in cost, but its low temperature resistance is poor; polyethylene has excellent electrical properties and chemical corrosion resistance, but its processing temperature window is narrow; polyurethane has excellent mechanical properties and wear resistance, but it is expensive and easily hydrolyzed. Among them, PVC has become the most commonly used cable outer sheath material due to its comprehensive performance and cost-effective advantages.

[0003] With the popularization of electronic devices and the development of communication technology, the problem of electromagnetic interference has become increasingly prominent. High-shielded cables achieve electromagnetic shielding by adding conductive fillers to the outer sheath to form a conductive network. The shielding effect mainly depends on the type, content and distribution of the conductive fillers. At present, conductive fillers mainly include metal powders, carbon fibers and conductive carbon black, among which conductive carbon black has become the most commonly used conductive filler due to its excellent conductive properties, low cost and stable chemical properties.

[0004] However, conductive carbon black has an inert surface and a large specific surface area, and there is serious agglomeration in the PVC matrix, which leads to the following problems: First, the dispersion of conductive carbon black in the PVC matrix is ​​poor, and the conductive network formed is uneven, requiring a higher addition amount to achieve the ideal shielding effect, but too high an addition amount will significantly reduce the mechanical properties and processing properties of the material; second, the interface bonding between the conductive carbon black and the PVC matrix is ​​poor, affecting the mechanical strength and durability of the composite material; third, the outer sheath materials of high-shielded cables on the market currently generally have problems such as unsatisfactory electromagnetic shielding effect and high cost.

[0005] CN110498989A discloses a PVC material for an ultra-high voltage cable outer sheath, comprising the following components in weight: 100 parts of polyvinyl chloride resin; 25-35 parts of a first plasticizer; 6-10 parts of a calcium zinc stabilizer; 0.3-0.5 parts of an antioxidant; 10-15 parts of calcium carbonate; 0.3-0.5 parts of a lubricant; 6-10 parts of a flame retardant; and 50-60 parts of a conductive black paste. The conductive black paste comprises a second plasticizer and conductive carbon black, and the conductive black paste is obtained by grinding the second plasticizer and the conductive carbon black, and the weight ratio of the second plasticizer to the conductive carbon black is 1.4-1.6:1, and the fineness of the conductive black paste is less than 15 μm.

[0006] There are also schemes in the prior art to improve the dispersibility and interfacial bonding of conductive carbon black in PVC by modifying it, but these modification methods are often too complicated or the effect is not ideal. Although some modification methods improve the dispersibility of conductive carbon black, they also reduce its conductivity; although some methods maintain the conductivity, they have poor compatibility with the PVC matrix and cannot obtain ideal comprehensive performance. In addition, most of the existing modification methods do not take into account the influence of the distribution state of conductive fillers in the composite material on the shielding performance, fail to achieve the directional distribution and enrichment of conductive fillers, and it is difficult to obtain excellent shielding effect at a low addition amount.

[0007] Therefore, it is urgent to develop a PVC-based composite material with excellent electromagnetic shielding properties, good mechanical properties and processing properties, while solving the problems of poor dispersion of conductive carbon black and poor interface bonding, to achieve effective distribution of conductive fillers and meet the application requirements of high-shielding cable outer sheaths. Summary of the invention

[0008] In order to solve the deficiencies in the prior art, the purpose of the present invention is to provide a PVC / polyester composite outer sheath material for high-shielded cables and a preparation method thereof. The material has excellent electromagnetic shielding performance and mechanical strength, and exhibits good weather resistance and corrosion resistance; has a wide processing window and excellent processing performance; while ensuring various performances, reduces the amount of conductive filler added, effectively reducing production costs. The composite outer sheath material of the present invention can meet various technical requirements of high-shielded cables and has important application value.

[0009] In order to achieve the above object, the present invention adopts the following technical solution:

[0010] A PVC / polyester composite outer sheath material for a high-shielded cable is made of the following components, measured in parts by weight: 100 parts of PVC, 30-50 parts of polypropylene adipate, 20-40 parts of inorganic filler, 4-12 parts of modified conductive carbon black, 1-3 parts of stabilizer, 1-3 parts of antioxidant, and 0.5-2 parts of silane coupling agent.

[0011] Preferably, the method for preparing the modified conductive carbon black comprises the following steps:

[0012] (1) adding conductive carbon black and 3-[3-carboxyallylamide]propyltriethoxysilane to anhydrous ethanol, performing ultrasonic dispersion treatment, adjusting the pH, stirring the reaction, filtering the product, washing with alcohol, and drying the product to obtain pretreated conductive carbon black;

[0013] Silane coupling pretreatment: The three ethoxy groups of 3-[3-carboxyallylamide]propyltriethoxysilane are first hydrolyzed under acidic conditions to generate active silanol groups (-Si-OH), which react with the hydroxyl groups (-OH) on the surface of carbon black to form stable Si-OC covalent bonds. At the same time, the carboxylallylamide group at the other end of the silane molecule remains free, thereby constructing an active layer with carboxyl functional groups on the surface of carbon black, which provide reaction sites for further modification.

[0014] Preferably, in step (1), the conductive carbon black is a high-purity conductive carbon black, with a DBP absorption value of 150-170 mL / 100 g, an ash content of <0.2%, and a 325-mesh sieve residue content of <8 ppm.

[0015] Preferably, in step (1), the amount ratio of conductive carbon black, 3-[3-carboxyallylamide]propyltriethoxysilane and anhydrous ethanol is 10 g: 0.5-3 g: 80-120 mL.

[0016] Preferably, in step (1), the ultrasonic treatment is performed for 10 to 30 minutes; the pH is adjusted to 4 to 6 with hydrochloric acid; and the stirring reaction conditions are 60 to 80° C. and 6 to 10 hours.

[0017] (2) adding pretreated conductive carbon black and perfluorohexyl ethyl acrylate to ethyl acetate, adding azobisisobutyronitrile under a nitrogen atmosphere, reflux reaction, filtering, washing and drying the product to obtain grafted conductive carbon black;

[0018] Fluoride grafting modification: The pretreated carbon black is subjected to a free radical grafting reaction with perfluorohexyl ethyl acrylate in ethyl acetate. In this process, azobisisobutyronitrile (AIBN) decomposes under heating conditions to produce free radicals, which initiate the free radical polymerization of perfluorohexyl ethyl acrylate monomers. These active free radicals undergo addition with the allyl groups introduced in the first step, and on the other hand, initiate the polymerization of the monomers, and finally form grafted perfluoroalkyl chains on the surface of carbon black. These fluorinated segments give the carbon black surface significant hydrophobic properties.

[0019] Preferably, in step (2), the usage ratio of pretreated conductive carbon black, perfluorohexylethyl acrylate, ethyl acetate, and azobisisobutyronitrile is 10 g: 5-12 g: 100-150 mL: 0.01-0.5 g.

[0020] Preferably, in step (2), the reflux reaction conditions are reflux reaction at 60-75° C. for 8-16 hours; and washing with ethyl acetate and deionized water for 3-5 times respectively.

[0021] (3) adding the grafted conductive carbon black and glyceryl monostearate to toluene, ultrasonically treating, adding p-toluenesulfonic acid, refluxing the reaction, cooling, centrifuging, washing and drying the product to obtain the modified conductive carbon black.

[0022] Surface encapsulation modification: The grafted carbon black is esterified with glyceryl monostearate in toluene. Under the catalysis of p-toluenesulfonic acid, the hydroxyl groups in glyceryl monostearate react with the carboxyl groups and other active groups remaining on the surface of carbon black to covalently graft the long-chain fatty acid groups to the surface of carbon black through ester bonds.

[0023] Preferably, in step (3), the usage ratio of grafted conductive carbon black, glyceryl monostearate, toluene and p-toluenesulfonic acid is 10 g: 3-9 g: 80-120 mL: 0.05-1 g.

[0024] Preferably, in step (3), the reflux reaction conditions are reflux reaction at 90-110° C. for 6-10 h; and washing with toluene and deionized water for 3-5 times respectively.

[0025] Preferably, the silane coupling agent is dodecyltriethoxysilane and / or hexadecyltriethoxysilane; the stabilizer is one or more of zinc stearate, calcium stearate, and calcium-zinc composite stabilizer; the antioxidant is one or more of phenolic antioxidants, phosphite antioxidants, and amine antioxidants; and the inorganic filler is one or more of aluminum hydroxide, magnesium hydroxide, calcium carbonate, talc, clay, mica, and kaolin.

[0026] The present invention also claims protection for a method for preparing the PVC / polyester composite outer sheath material for the high-shielded cable, comprising the following steps: adding PVC, polypropylene adipate, modified conductive carbon black, stabilizer, and antioxidant into a kneader and stirring and mixing evenly at 140-160° C., then adding inorganic filler and silane coupling agent, kneading and stirring evenly, extruding and molding at 160-180° C., cooling and pelletizing, to obtain the PVC / polyester composite outer sheath material for the high-shielded cable.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention provides a PVC / polyester composite outer sheath material for high-shielded cables, which has excellent comprehensive performance through the synergistic effect of various components: PVC as a base resin has good mechanical strength and weather resistance; polypropylene adipate as a plasticizer can not only improve the flexibility and processing performance of PVC, but also improve the low-temperature resistance of the material; the addition of inorganic fillers significantly improves the flame retardant performance and mechanical strength of the material, while reducing the production cost; the introduction of modified conductive carbon black gives the material excellent electromagnetic shielding performance and corrosion resistance; the stabilizer effectively prevents the thermal degradation of PVC during processing and use, and prolongs the service life of the material; the addition of antioxidants improves the anti-aging performance of the material; the use of silane coupling agents improves the interface bonding between the organic phase and the inorganic phase, and improves the mechanical properties and aging resistance of the composite material. The proportion of each component is optimized and designed, so that the composite material has excellent processing performance, mechanical strength, weather resistance and electromagnetic shielding performance, and meets the application requirements of the outer sheath of high-shielded cables.

[0029] 2. The present invention provides a modified conductive carbon black. In the first step, carboxyl groups and double bond functional groups are introduced on the surface of carbon black by grafting 3-[3-carboxyallylamide]propyltriethoxysilane, thereby increasing the active sites on the surface of carbon black and providing chemical reaction sites for subsequent modification. In the second step, perfluorohexylethyl acrylate is used to react with the double bonds on the surface by free radical addition to introduce perfluoroalkyl chains on the surface of carbon black. Since the fluorine-containing groups have the characteristic of migrating to the surface of the material during the film-forming process, the modified carbon black is enriched on the surface of the material. The fluorine-containing groups enriched on the surface It also provides excellent hydrophobicity, effectively preventing the intrusion of corrosive substances in the air and improving the corrosion resistance of the material; in the third step, through the esterification reaction of monostearate glycerol, an ester group with surface migration characteristics is introduced, which cooperates with the fluorine-containing group to promote the migration of conductive carbon black to the surface of the material, forming an efficient surface conductive network, significantly enhancing the electromagnetic shielding effect of the cable, and through the introduction of long-chain alkyl groups, the interpenetration effect between the molecular chains is utilized to enhance the compatibility and interfacial bonding between the modified conductive carbon black and the PVC matrix, thereby improving the mechanical properties of the composite material. This multifunctional and synergistic surface modification design enables the modified conductive carbon black to achieve excellent conductivity and electromagnetic shielding effects at a relatively low addition amount, while significantly improving the comprehensive performance of the composite material. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0031] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.

[0032] PVC was purchased from Xinjiang Tianye Group Co., Ltd., with a degree of polymerization of 2000-2200;

[0033] The calcium zinc composite stabilizer is purchased from the German Xiongpai Company, brand MC 8890 or MC 9700;

[0034] The aluminum hydroxide particle size is 25 μm and is purchased from Shandong Keheng Crystal Material Technology Co., Ltd. A method for preparing a PVC / polyester composite outer sheath material for a high-shielded cable comprises the following steps:

[0035] (1) Add 10 g of conductive carbon black and 0.5-3 g of 3-[3-carboxyallylamide]propyltriethoxysilane to 80-120 mL of anhydrous ethanol, perform ultrasonic dispersion treatment for 10-30 min, adjust the pH to 4-6 with hydrochloric acid, stir and react at 60-80° C. for 6-10 h, filter, wash with alcohol, and dry the product to obtain pretreated conductive carbon black;

[0036] (2) Add 10 g of pretreated conductive carbon black and 5-12 g of perfluorohexyl ethyl acrylate to 100-150 mL of ethyl acetate, add 0.01-0.5 g of azobisisobutyronitrile under nitrogen atmosphere, reflux at 60-75 °C for 8-16 h, filter the product, wash with ethyl acetate and deionized water for 3-5 times respectively, and dry to obtain grafted conductive carbon black;

[0037] (3) Add 10 g of grafted conductive carbon black and 3-9 g of glyceryl monostearate to 80-120 mL of toluene, perform ultrasonic treatment, add 0.05-1 g of p-toluenesulfonic acid, and reflux for 6-10 h at 90-110 °C. Cool and centrifuge the product, wash it with toluene and deionized water for 3-5 times, respectively, and dry it to obtain modified conductive carbon black.

[0038] (4) Add 100 parts of PVC, 30-50 parts of polypropylene adipate, 4-12 parts of modified conductive carbon black, 1-3 parts of stabilizer and 1-3 parts of antioxidant into a kneader, stir and mix evenly at 140-160° C., then add 20-40 parts of inorganic filler and 0.5-2 parts of silane coupling agent, knead and stir evenly, extrude and shape at 160-180° C., cool and pelletize to obtain the PVC / polyester composite outer sheath material for high-shielded cable.

[0039] The silane coupling agent is dodecyltriethoxysilane and / or hexadecyltriethoxysilane; the stabilizer is one or more of zinc stearate, calcium stearate, and calcium-zinc composite stabilizer; the antioxidant is one or more of phenolic antioxidants, phosphite antioxidants, and amine antioxidants; and the inorganic filler is one or more of aluminum hydroxide, magnesium hydroxide, calcium carbonate, talc, clay, mica, and kaolin.

[0040] The present invention will be further described below through specific embodiments.

[0041] Example 1

[0042] A method for preparing a PVC / polyester composite outer sheath material for a high-shielded cable comprises the following steps:

[0043] (1) 10 g of conductive carbon black and 3 g of 3-[3-carboxyallylamide]propyltriethoxysilane were added to 100 mL of anhydrous ethanol, and the mixture was subjected to ultrasonic dispersion treatment for 20 min. The pH value was adjusted to 5 with hydrochloric acid, and the mixture was stirred at 80° C. for 6 h. The product was filtered, washed with alcohol, and dried to obtain pretreated conductive carbon black.

[0044] (2) Add 10 g of pretreated conductive carbon black and 12 g of perfluorohexyl ethyl acrylate to 100 mL of ethyl acetate, add 0.5 g of azobisisobutyronitrile under nitrogen atmosphere, reflux at 75 °C for 8 h, filter the product, wash it with ethyl acetate and deionized water for 4 times respectively, and dry it to obtain grafted conductive carbon black;

[0045] (3) Add 10 g of grafted conductive carbon black and 9 g of glycerol monostearate to 100 mL of toluene, perform ultrasonic treatment, add 1 g of p-toluenesulfonic acid, and reflux for 6 h at 110 °C. Cool and centrifuge the product, wash it 4 times with toluene and deionized water respectively, and dry it to obtain modified conductive carbon black.

[0046] (4) Add 1000 g PVC, 500 g poly(propylene adipate), 120 g modified conductive carbon black, 30 g calcium zinc composite stabilizer, and 30 g antioxidant 1010 into a kneader and stir to mix evenly at 150° C., then add 400 g aluminum hydroxide and 20 g hexadecyltriethoxysilane, knead and stir evenly, extrude and shape at 170° C., cool and pelletize to obtain the PVC / polyester composite outer sheath material for the high-shielded cable.

[0047] Example 2

[0048] A method for preparing a PVC / polyester composite outer sheath material for a high-shielded cable comprises the following steps:

[0049] (1) Add 10 g of conductive carbon black and 2 g of 3-[3-carboxyallylamide]propyltriethoxysilane to 100 mL of anhydrous ethanol, perform ultrasonic dispersion treatment for 20 min, adjust the pH to 5 with hydrochloric acid, stir and react at 70° C. for 8 h, filter, wash with alcohol, and dry the product to obtain pretreated conductive carbon black;

[0050] (2) 10 g of pretreated conductive carbon black and 10 g of perfluorohexyl ethyl acrylate were added to 100 mL of ethyl acetate, and 0.4 g of azobisisobutyronitrile was added under a nitrogen atmosphere. The mixture was refluxed at 70 °C for 10 h. The product was filtered, washed with ethyl acetate and deionized water for 4 times, and dried to obtain grafted conductive carbon black.

[0051] (3) Add 10 g of grafted conductive carbon black and 8 g of glycerol monostearate to 100 mL of toluene, perform ultrasonic treatment, add 0.6 g of p-toluenesulfonic acid, and reflux for 8 h at 100 °C. Cool and centrifuge the product, wash it 4 times with toluene and deionized water respectively, and dry it to obtain modified conductive carbon black.

[0052] (4) Add 1000 g PVC, 450 g poly(propylene adipate), 100 g modified conductive carbon black, 25 g calcium zinc composite stabilizer, and 25 g antioxidant 1010 into a kneader and stir to mix evenly at 150 ° C. Then add 350 g aluminum hydroxide and 15 g hexadecyltriethoxysilane. After kneading and stirring evenly, extrude and shape at 170 ° C., cool and pelletize to obtain the PVC / polyester composite outer sheath material for the high-shielded cable.

[0053] Example 3

[0054] A method for preparing a PVC / polyester composite outer sheath material for a high-shielded cable comprises the following steps:

[0055] (1) Add 10 g of conductive carbon black and 1 g of 3-[3-carboxyallylamide]propyltriethoxysilane to 100 mL of anhydrous ethanol, perform ultrasonic dispersion treatment for 20 min, adjust the pH to 5 with hydrochloric acid, stir and react at 70° C. for 9 h, filter, wash with alcohol, and dry the product to obtain pretreated conductive carbon black;

[0056] (2) Add 10 g of pretreated conductive carbon black and 8 g of perfluorohexyl ethyl acrylate to 100 mL of ethyl acetate, add 0.3 g of azobisisobutyronitrile under nitrogen atmosphere, reflux at 65 °C for 12 h, filter the product, wash it with ethyl acetate and deionized water for 4 times respectively, and dry it to obtain grafted conductive carbon black;

[0057] (3) 10 g of grafted conductive carbon black and 5 g of glycerol monostearate were added to 100 mL of toluene, and ultrasonic treatment was performed. 0.4 g of p-toluenesulfonic acid was added, and the mixture was refluxed at 100 °C for 9 h. The product was cooled and centrifuged, and washed with toluene and deionized water for 4 times, respectively, and dried to obtain modified conductive carbon black.

[0058] (4) Add 1000 g PVC, 360 g poly(propylene adipate), 60 g modified conductive carbon black, 16 g calcium zinc composite stabilizer, and 16 g antioxidant 1010 into a kneader and stir to mix evenly at 150° C., then add 260 g aluminum hydroxide and 10 g hexadecyltriethoxysilane, knead and stir evenly, extrude and shape at 170° C., cool and pelletize to obtain the PVC / polyester composite outer sheath material for the high-shielded cable.

[0059] Example 4

[0060] A method for preparing a PVC / polyester composite outer sheath material for a high-shielded cable comprises the following steps:

[0061] (1) Add 10 g of conductive carbon black and 0.5 g of 3-[3-carboxyallylamide]propyltriethoxysilane to 100 mL of anhydrous ethanol, perform ultrasonic dispersion treatment for 20 min, adjust the pH to 5 with hydrochloric acid, stir and react at 60° C. for 10 h, filter, wash with alcohol, and dry the product to obtain pretreated conductive carbon black;

[0062] (2) Add 10 g of pretreated conductive carbon black and 5 g of perfluorohexyl ethyl acrylate to 100 mL of ethyl acetate, add 0.1 g of azobisisobutyronitrile under nitrogen atmosphere, reflux at 60 °C for 16 h, filter the product, wash it with ethyl acetate and deionized water for 4 times respectively, and dry it to obtain grafted conductive carbon black;

[0063] (3) Add 10 g of grafted conductive carbon black and 3 g of glycerol monostearate to 100 mL of toluene, perform ultrasonic treatment, add 0.05 g of p-toluenesulfonic acid, and reflux for 10 h at 90 °C. Cool and centrifuge the product, wash it with toluene and deionized water for 4 times, and dry it to obtain modified conductive carbon black.

[0064] (4) Add 1000 g PVC, 300 g poly(propylene adipate), 40 g modified conductive carbon black, 10 g calcium zinc composite stabilizer, and 10 g antioxidant 1010 into a kneader and stir to mix evenly at 150° C., then add 200 g aluminum hydroxide and 5 g hexadecyltriethoxysilane, knead and stir to mix evenly, extrude and shape at 170° C., cool and pelletize to obtain the PVC / polyester composite outer sheath material for the high-shielded cable.

[0065] Comparative Example 1

[0066] A method for preparing a PVC / polyester composite outer sheath material comprises the following steps:

[0067] (1) 10 g of conductive carbon black and 3 g of 3-[3-carboxyallylamide]propyltriethoxysilane were added to 100 mL of anhydrous ethanol, and the mixture was subjected to ultrasonic dispersion treatment for 20 min. The pH value was adjusted to 5 with hydrochloric acid, and the mixture was stirred at 80° C. for 6 h. The product was filtered, washed with alcohol, and dried to obtain pretreated conductive carbon black.

[0068] (2) Add 10 g of pretreated conductive carbon black and 12 g of perfluorohexyl ethyl acrylate to 100 mL of ethyl acetate, add 0.5 g of azobisisobutyronitrile under nitrogen atmosphere, reflux at 75 °C for 8 h, filter the product, wash it with ethyl acetate and deionized water for 4 times respectively, and dry it to obtain grafted conductive carbon black;

[0069] (3) Add 1000 g PVC, 500 g poly(propylene adipate), 120 g grafted conductive carbon black, 30 g calcium zinc composite stabilizer, and 30 g antioxidant 1010 into a kneader and stir to mix evenly at 150 °C. Then add 400 g aluminum hydroxide and 20 g hexadecyltriethoxysilane. After kneading and stirring evenly, extrude and shape at 170 °C, cool and pelletize to obtain a PVC / polyester composite outer sheath material.

[0070] Comparative Example 2

[0071] A method for preparing a PVC / polyester composite outer sheath material comprises the following steps:

[0072] (1) 10 g of conductive carbon black and 3 g of 3-[3-carboxyallylamide]propyltriethoxysilane were added to 100 mL of anhydrous ethanol, and the mixture was subjected to ultrasonic dispersion treatment for 20 min. The pH value was adjusted to 5 with hydrochloric acid, and the mixture was stirred at 80° C. for 6 h. The product was filtered, washed with alcohol, and dried to obtain pretreated conductive carbon black.

[0073] (2) 10 g of pretreated conductive carbon black and 9 g of glycerol monostearate were added to 100 mL of toluene, ultrasonically treated, 1 g of p-toluenesulfonic acid was added, and refluxed at 110 °C for 6 h. The product was cooled and centrifuged, washed with toluene and deionized water for 4 times respectively, and dried to obtain modified conductive carbon black;

[0074] (3) Add 1000 g of PVC, 500 g of polypropylene adipate, 120 g of modified conductive carbon black, 30 g of calcium zinc composite stabilizer, and 30 g of antioxidant 1010 into a kneader and stir to mix evenly at 150° C., then add 400 g of aluminum hydroxide and 20 g of hexadecyltriethoxysilane, knead and stir to mix evenly, extrude and shape at 170° C., cool and pelletize to obtain the PVC / polyester composite outer sheath material.

[0075] Comparative Example 3

[0076] A method for preparing a PVC / polyester composite outer sheath material comprises the following steps:

[0077] (1) 10 g of conductive carbon black and 3 g of 3-[3-carboxyallylamide]propyltriethoxysilane were added to 100 mL of anhydrous ethanol, and the mixture was subjected to ultrasonic dispersion treatment for 20 min. The pH value was adjusted to 5 with hydrochloric acid, and the mixture was stirred at 80° C. for 6 h. The product was filtered, washed with alcohol, and dried to obtain pretreated conductive carbon black.

[0078] (2) Add 1000 g of PVC, 500 g of polypropylene adipate, 120 g of pretreated conductive carbon black, 30 g of calcium zinc composite stabilizer, and 30 g of antioxidant 1010 into a kneader and stir to mix evenly at 150° C., then add 400 g of aluminum hydroxide and 20 g of hexadecyltriethoxysilane, knead and stir to mix evenly, extrude and shape at 170° C., cool and pelletize to obtain the PVC / polyester composite outer sheath material.

[0079] The composite outer sheath materials obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were made into test pieces. The tensile strength and elongation at break were tested using an electronic universal testing machine with reference to GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets", with a tensile rate of 250 mm / min and a gauge length of 20 mm. The volume resistance of the samples in an oil bath at 20°C and 90°C was tested using a resistivity tester with reference to GB / T 3048.3-2007 "Test methods for electrical properties of wires and cables Part 3: Volume resistivity test of semi-conductive rubber and plastic materials". The electromagnetic wave shielding effectiveness test was performed with reference to GB / T 30142-2013 "Measurement method for shielding effectiveness of planar electromagnetic shielding materials"; the electromagnetic wave shielding effectiveness test was performed using reference to GB / T 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test" uses a limiting oxygen index tester to test the limiting oxygen index; the sample is immersed in 25wt% hydrochloric acid solution, 25wt% sodium hydroxide solution, 25wt% sodium chloride solution and water solution under the same conditions for 300h, and then taken out to observe the surface corrosion. The specific results are shown in Table 1.

[0080] Table 1 Test results of outer sheath material performance

[0081]

[0082] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A PVC / polyester composite outer sheath material for high-shielded cables, characterized in that: The invention is prepared from the following components by weight: 100 parts of PVC, 30-50 parts of polypropylene adipate, 20-40 parts of inorganic filler, 4-12 parts of modified conductive carbon black, 1-3 parts of stabilizer, 1-3 parts of antioxidant, and 0.5-2 parts of silane coupling agent; The preparation method of the modified conductive carbon black comprises the following steps: (1) adding conductive carbon black and 3-[3-carboxyallylamide]propyltriethoxysilane to anhydrous ethanol, performing ultrasonic dispersion treatment, adjusting the pH, stirring the reaction, filtering the product, washing with alcohol, and drying the product to obtain pretreated conductive carbon black; (2) adding pretreated conductive carbon black and perfluorohexyl ethyl acrylate to ethyl acetate, adding azobisisobutyronitrile under a nitrogen atmosphere, reflux reaction, filtering, washing and drying the product to obtain grafted conductive carbon black; (3) adding the grafted conductive carbon black and glyceryl monostearate to toluene, ultrasonically treating, adding p-toluenesulfonic acid, refluxing the reaction, cooling, centrifuging, washing and drying the product to obtain the modified conductive carbon black.

2. The PVC / polyester composite outer sheath material for high-shielded cables according to claim 1, characterized in that: In step (1), the conductive carbon black is a high-purity conductive carbon black, with a DBP absorption value of 150-170 mL / 100 g, an ash content of <0.2%, and a 325-mesh sieve residue content of <8 ppm.

3. The PVC / polyester composite outer sheath material for high-shielded cables according to claim 1, characterized in that: In step (1), the amount ratio of conductive carbon black, 3-[3-carboxyallylamide]propyltriethoxysilane and anhydrous ethanol is 10g:0.5~3g:80~120mL.

4. The PVC / polyester composite outer sheath material for high-shielded cables according to claim 1, characterized in that: In step (1), ultrasonic treatment is performed for 10 to 30 minutes; the pH is adjusted to 4 to 6 with hydrochloric acid; and the stirring reaction conditions are 60 to 80° C. and the stirring reaction is performed for 6 to 10 hours.

5. The PVC / polyester composite outer sheath material for high-shielded cables according to claim 1, characterized in that: In step (2), the amount ratio of pretreated conductive carbon black, perfluorohexylethyl acrylate, ethyl acetate, and azobisisobutyronitrile is 10 g: 5-12 g: 100-150 mL: 0.01-0.5 g.

6. The PVC / polyester composite outer sheath material for high-shield cables according to claim 1, characterized in that: In step (2), the reflux reaction conditions are reflux reaction at 60-75° C. for 8-16 hours; and washing with ethyl acetate and deionized water for 3-5 times respectively.

7. The PVC / polyester composite outer sheath material for high-shield cables according to claim 1, characterized in that: In step (3), the usage ratio of grafted conductive carbon black, glyceryl monostearate, toluene and p-toluenesulfonic acid is 10 g: 3-9 g: 80-120 mL: 0.05-1 g.

8. The PVC / polyester composite outer sheath material for high-shield cables according to claim 1, characterized in that: In step (3), the reflux reaction conditions are reflux reaction at 90-110° C. for 6-10 h; and washing with toluene and deionized water for 3-5 times respectively.

9. A method for preparing a PVC / polyester composite outer sheath material for a high-shielded cable as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following steps: adding PVC, polypropylene adipate, modified conductive carbon black, a stabilizer and an antioxidant into a kneader, stirring and mixing evenly at 140-160° C., then adding an inorganic filler and a silane coupling agent, kneading and stirring evenly, extruding and molding at 160-180° C., cooling and pelletizing, and obtaining the PVC / polyester composite outer sheath material for the high-shielded cable.

Citation Information

Patent Citations

  • PVC material for extra-high voltage cable outer sheath and preparation method thereof

    CN110498989A

  • Graphene multifunctional polyurethane fiber and preparation method thereof

    CN110904532A

  • High-temperature-resistant low-smoke low-halogen crosslinked cable material as well as preparation and application thereof

    CN117209880A